Identifying an optimal treatment for schizophrenia: A 2-year randomized controlled trial comparing integrated care to a high-quality routine treatment - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2011)
Objective. This study used repeated outcome measures over a 2-year period to compare the clinical and social benefits of routine schizophrenia treatment with those of evidence-based pharmacological and psychosocial treatment strategies. Method. One hundred patients who were diagnosed with schizophrenia according to DSM-IV criteria were randomly assigned to 24 months of either optimal case management (OCM) or routine case management (RCM). OCM involved minimally effective doses of antipsychotic medication with compliance training, an identical treatment programme with the addition of manual-based communication and problem solving training to help patients and caregivers manage stress, social skills training, supported employment, cognitive-behavioural strategies for residual psychotic and non-psychotic symptoms, as well as anger management and substance use counselling. RCM involved minimally effective doses of antipsychotic medication with compliance training, the monitoring of side effects, education about schizophrenia and its optimal treatment, detection of early warning signs and supportive psychotherapy to address practical problems. The symptoms, impairment, disability, unmet needs, quality of life of the patients were examined by blinded researchers every 6 months. Results. Statistically and clinically significant advantages were observed for OCM versus RCM on all measures. Most of these advantages increased throughout the 24-month period. Conclusions. This study helps demonstrate the importance of psychosocial interventions in the treatment of schizophrenia. Recent advances in evidence-based psychosocial strategies can be implemented into routine clinical practice with additional clinical and social benefits.
Keywords: Schizophrenia; optimal treatment; integrated care; cognitive behavioural therapy; COGNITIVE-BEHAVIORAL THERAPY; PERSONAL THERAPY; 3-YEAR TRIALS; FAMILY; COMMUNITY; RELAPSE; RELIABILITY; INSTRUMENT; COMPONENTS; VALIDITY